Performing experiences among music performance student and its influence toward their development / Muhammad Fikri Azim Mohd Akhir - Mohd Akhir, Muhammad Fikri Azim (2020)
This paper will review the empirical evidence relating the perception of the student about their experience in performance and the effect that have helped them toward their development in UiTM. To get an exact data, quantitative method had been used which is collected through a survey questionnaire. The sample that involved was 40 people fromMU222 final year student. After analyzing the relate data, it shows subject interest toward live performance and reasons why they like or do not like it. It also had explained about type of experience and how long the performer had learned music have a relation toward their knowledge, effectiveness of practice, preparation before performance, confident level, ethical as performer, skill, their preparation in future, quality of performance on stage, mental and physical preparation and effect after the performance. Besides that, data had shown subject suggest that self-discipline, good confident, social skill, good teamwork, time management and stay focus was element needed to become successful performer. Overall, it can be concluded that positive effect that given to the subject through experience had make them prepared and mature enough to be a performer in future.